European Union politics - McCormick, John 1954- (Palgrave Macmillan, 2011)
"This major new text provides an authoritative introduction to all aspects of politics and policy in the European Union. Written in the author's inimitably accessible style, it brings the European Union to life, giving readers a sense of the color and flavor of European Union politics and its impact on the citizens of Europe. * A major new introductory text specifically designed for students studying the European Union for the first time * Broad and detailed coverage of all aspects of European Union politics and policy and the nature of European integration * Written in the author's inimitably lively and accessible style - an extremely student-friendly new addition to a generally dry and dusty field * Readable and relevant, and alive to the human side of the European Union and the impact it has on the lives of Europe's citizens * Packed with a wide range of maps, charts, photos, and boxed features, including profiles of key figures in the theory and practice of European integration and country profiles of member states * Companion website includes updated materials, self test questions and answers, a searchable chronology glossary of terms, weblinks, and further reading and an instructor's site providing additional teaching resources"--Provided by publisher.